Tangible Long-Lived Asset Impairments and Future Operating Cash Flows under U.S. GAAP and IFRS - Gordon, Elizabeth A.; Hsu, Hsiao-Tang (The Accounting Review, 2018)
ABSTRACT This paper investigates the predictive value of tangible long-lived asset impairments for changes in future operating cash flows under U.S. GAAP and IFRS. We find that impairments reported under IFRS are negatively associated with changes in future operating cash flows, whereas those under U.S. GAAP, on average, are not. We investigate whether differences in the predictive value are attributable to differences in recognition or measurement, providing evidence suggesting that impairment recognition under U.S. GAAP is delayed. Evidence also suggests that the value-in-use measurement attribute, allowed under IFRS, does not induce under-impairing as IFRS and U.S. GAAP impairments are similarly related to future impairments. The main result of a negative association under IFRS, but not U.S. GAAP, holds after considering future impairments to control for measurement differences, macro-economic factors, and firm reporting incentives. Further, impairment losses under IFRS are more predictive in high-enforcement countries. JEL Classifications: D78; F02; M16; M41; G38. Data Availability: Data used are available from sources identified in the paper.